Lean Strategy for Optimizing Response Time in Hospital Code Blue Activation: A Two-Cycle Action Research in Central Java, Indonesia - Habib Laksmana Prima; Merita Arini (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
ntroduction: Inefficiencies or delays in Code Blue activation for cardiac arrest patients contribute significantly to increased mortality. Rapid response time is closely associated with better prognosis. However, no previous study has systematically addressed the problem of Code Blue activation delay using a structured approach in hospital settings. This study aimed to formulate and implement improvement strategies to minimize waste and accelerate Code Blue activation. Methods: This research employed an action research design and adopted a two-cycle action research design to validate the application of Lean Management in optimizing Code Blue activation at a private Type D hospital in Banyumas, Central Java, Indonesia. A total of 11 consecutive Code Blue cases were observed in each cycle — 11 cases before (Cycle 1) and 11 cases after intervention (Cycle 2). Each cycle consisted of four stages: diagnosis, planning, action, and evaluation, guided by Value Stream Mapping (VSM) to identify and eliminate waste. Quantitative data (lead time, waiting time, cycle time, and Value-Added Ratio) were analyzed using Mann–Whitney tests, while qualitative insights were obtained from in depth interview and focus group discussions with 20 healthcare professionals. Results: The top three critical wastes identified in the baseline assessment were waiting (20.7%), defects (20.4%), and transportation (17%). Thus, waiting was concluded to be the most critical waste in the Code Blue activation process. Initially, the activation process had four phases: initial assessment by inpatient nurse, assessment by ward doctor, system activation, and arrival of the secondary team. After interventions, it was streamlined to three phases by removing the ward doctor’s assessment. Post-intervention, response time dropped by 92.2 % (from 122.1 to 9.5 minutes, p < 0.001), waiting time decreased by 91.3 % (from 50.7 to 4.4 minutes, p < 0.001), and the Value-Added Ratio (VAR) increased from 7 % to 39 % (p < 0.001). Conclusion: The implementation of Lean Management significantly reduces response time in Code Blue activation. Sustaining these improvements requires ongoing commitment and a multidimensional approach, including training, system evaluation, and strengthening a supportive work culture.